Ventricular tachyarrhythmia and sudden cardiac death with domperidone use in Parkinson's disease. (19th May 2016) - Renoux, Christel; Dell'Aniello, Sophie; Khairy, Paul; Marras, Connie; Bugden, Shawn; Turin, Tanvir Chowdhury; Blais, Lucie; Tamim, Hala; Evans, Charity; Steele, Russell; Dormuth, Colin; Ernst, Pierre; et al.
Abstract : Aim: Domperidone is preferentially used over other antiemetic agents to treat digestive symptoms in Parkinson's disease (PD). Concerns have been raised regarding an increased risk of ventricular tachyarrhythmia and sudden cardiac death (VT/SCD) associated with domperidone in the general population. However, the risk in PD is unknown. Methods: We conducted a multicentre retrospective cohort study using administrative databases from seven Canadian provinces and the UK Clinical Practice Research Datalink. Using a nested case–control analysis, we estimated the rate ratios (RRs) of VT/SCD associated with domperidone use compared to no use in patients newly‐diagnosed with PD. VT/SCD events were identified using administrative medical records and vital statistics with a manual review of all potential cases. Meta‐analytic methods were used to estimate overall effects across sites. Results: Among 214 962 patients with PD, 2907 cases of VT/SCD were identified during 886 581 person‐years of follow‐up (incidence rate 3.28 per 1000 persons per year). Current use of domperidone was associated with a non‐statistically significant 22% increased risk of VT/SCD (RR 1.22; 95% CI 0.99–1.50) compared with no use. The risk was significantly elevated in those with a history of cardiovascular disease (RR 1.38; 95% CI 1.07–1.78), but not in those without (RR 1.21; 95% CI 0.81–1.81). Dose and duration of use did not affect the magnitude of the risk. Conclusion: Domperidone use may increase the risk of VT/SCD in patients with PD, particularly those with a history of cardiovascular disease. This risk may be underestimated because of imprecision in identifying VT/SCD events.